Strategi Penggunaan Mind Mapping Dalam Pembelajaran Pendidikan Agama Islam Untuk Memperkuat Pemahaman Naratif Siswa Di SMA Negeri 1 Kencong - Nurhaibah, Ananda Diva; Hakim, Faisol (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study aims to understand the strategy of using mind mapping in learning Islamic Religious Education (PAI) as an effort to strengthen students' narrative understanding at SMA Negeri 1 Kencong. Mind mapping is positioned as a visual approach that is able to assist students in organiz-ing, understanding, and internalizing narrative materials such as stories of prophets, Islamic history, and religious values in a reflective manner. This study used descriptive qualitative method with data collection techniques through interviews with three teachers and a number of students, as well as observation of the learning process in the classroom. The results show that mind mapping not only improves higher-order thinking skills such as moral analysis and reflection, but also encourages students' cognitive, affective and spiritual engagement as a whole. Teachers play an important role in guiding the process of making mind maps, starting from the pre-learning stage, during learning, to post-learning. Findings also show that students who use mind mapping have stronger memory, are better able to understand the relationship between concepts, and show improvement in retelling the content of the narrative logically and contextually. Nevertheless, some obstacles were found, such as students' limited visu-alization ability and the tendency to focus on aesthetic aspects. However, these obstacles can be overcome through teacher assistance and the provision of supportive learning media. In conclusion, the mind mapping strategy effectively strengthens students' narrative comprehension in PAI learning by integrating visual, constructivistic, and contextual approaches in an integrated manner.